Carrier Shifting Algorithms for the Mitigation of Circulating Current in Diode Clamped MLI fed Induction Motor Drive - C. Santhakumar; R. Shivakumar; C. Bharatiraja; P. Sanjeevikumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Reduction of circulating current is one of the major considerations in inverter fed electrical drives. Diode clamped MLI enables higher output current per phase, thereby rating of the drive gets increased effectively. Various methods of triggering in the inverter legs creates better voltage profile and leads to the enabling of circulating current in the drive system.  The induced circulating current flows through the apparatus neutral (N) and supply ground (G) is caused by the existence of parasitic capacitance. This circulating current may cause potential danger especially when parasitic capacitance poses large. In the past, different modulation techniques and conversion topologies have been introduced to minimize the flow of circulating current. However, these techniques lead to complexity, high cost, low voltage profile and efficiency due to lower modulation parameters. This paper proposes PS, POD, PD carrier shifting PWM algorithms for diode clamped MLI to tumbling the circulating current within the each phase of inverter legs. The performances of proposed algorithm, in terms of circulating current, THD, losses and efficiencies are analyzed theoreticallyand are validated via simulation and experimental results.